Η βυζαντινή οικογένεια των Αγιοθεοδωριτών (Ι): Νικόλαος Αγιοθεοδωρίτης, Πανιερώτατος Μητροπολίτης Αθηνών και Υπέρτιμος - ΜΑΔΑΡΙΑΓΑ, Ελισάβετ (Byzantina Symmeikta, 2010)
THE BYZANTINE FAMILY OF THE HAGIOTHEODORITES (I): NIKOLAOS HAGIOTHEODORITES, ALL-HOLIEST METROPOLITAN OF ATHENS AND HYPERTIMOS The present article consists in a prosopographical study on Nikolaos Hagiotheodorites. Nikolaos, didaskalos tou evangeliou, maistor ton rhetoron and metropolitan of Athens (1160/66-1175), was one of the most prominent scholars under the service of the Ecumenical Patriarchate in Constantinople. His brother Michael acted as a Logothetes tou dromou (1166-1180) and mesazon in the court of Manuel I Comnenus. Both of them are the most renowned members of the Hagiotheodorites family. Nikolaos Hagiotheodorites was the typical busy public figure of his time. Having initially a succesful church career, he then accomplished an impressive professional activity by combining many secular and ecclesiastical offices.